Activation of low grade clays at high temperatures - Castillo, Rancés; Fernández, Rodrigo; Antoni, Mathieu; Scrivener, Karen; Alujas, Adrián; Martirena, José F. (Revista Ingeniería de Construcción, 2010)
This paper introduces a proposal to produce artificial pozzolans by means of activation of low grade clays, as an alternative to metakaolin production. Basically the work considered clay mineral enriched soils, mainly kaolin. Such material was sediment and later calcined at 900 Celsius degrees. The same process was conducted with non-sediment material. Due to calcinations, the specific surface decreased significantly, and therefore, its pozzolanic activity, which was assessed by monitoring the CH consumption in cement pastes of several ages, as well as compressive strength in cement mortars. Calcined material, apparently inert, was ground until achieving high finesse. An experimental series made of sugar cane straw ash was introduced, as a reference to the pozzolans previously studied. Ground calcined clays increased its pozzolanic activity at a huge extent, which is characterized by a higher consumption of CH in cement pastes and by a higher compressive strength in cement mortars. Apparently this change takes place due to grinding effect on the reactivity of calcined clayey soils. The best results were obtained from sediment samples before their calcinations. The compressive strength of cement mortars, replacing a 30% the cement weight by such material, is similar to the control (100% cement) at 7 days, and higher at 28 and 60 days. Although such replacement does not decrease total porosity, it does decrease sorptivity, mainly in samples produced with calcined and ground sedimented material. Probably this phenomenon occurs because of pores capillary refining process induced by the precipitation of products of pozzolanic reaction.